2003
DOI: 10.1063/1.1589178
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and nonlinear optical properties of nanoparticle silver oxide films

Abstract: We report the fabrication of nanoparticle silver oxide thin films by rf magnetron sputtering and characterization of their nonlinear optical properties. The chemical decomposition and reversibility of AgO x compounds were studied by thermogravimetric analysis, differential scanning calorimetry, and x-ray diffraction. Electron spectroscopy for chemical analysis measurements revealed a 0.5 eV negative binding energy shift from AgO to Ag 2 O phase. The effect of particle plasmon resonance was confirmed by the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 24 publications
4
26
0
Order By: Relevance
“…Different decomposition temperatures of Ag oxides such as 210 • C [75], 250 • C [86,90], 280 • C [18], 330 • C [91], 385 • C [92], 454 • C [93] have been reported in the literature. The exact decomposition temperature and mechanism of Ag oxides to Ag depends on several factors like the preparation method of the Ag oxide particles, different analysis methods, mechanical ageing conditions, partial pressure of gases like oxygen or CO 2 [92][93][94].…”
Section: Tensile Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Different decomposition temperatures of Ag oxides such as 210 • C [75], 250 • C [86,90], 280 • C [18], 330 • C [91], 385 • C [92], 454 • C [93] have been reported in the literature. The exact decomposition temperature and mechanism of Ag oxides to Ag depends on several factors like the preparation method of the Ag oxide particles, different analysis methods, mechanical ageing conditions, partial pressure of gases like oxygen or CO 2 [92][93][94].…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Different decomposition temperatures of Ag oxides such as 210 • C [75], 250 • C [86,90], 280 • C [18], 330 • C [91], 385 • C [92], 454 • C [93] have been reported in the literature. The exact decomposition temperature and mechanism of Ag oxides to Ag depends on several factors like the preparation method of the Ag oxide particles, different analysis methods, mechanical ageing conditions, partial pressure of gases like oxygen or CO 2 [92][93][94]. Regarding testing methods, dynamic heating methods with differential scanning calorimetry (DSC) and thermo-gravimetric analyser (TGA) normally produces a higher decomposition temperature, as much as 50 • C more than isothermal heating methods, which is followed by phase identification with X-ray diffractometer (XRD), Raman spectroscopy or Fourier transform infra-red (FTIR) spectroscopy [93].…”
Section: Tensile Strengthmentioning
confidence: 99%
“…These results confirm that Ag 2 O films could be used as a nanoscale optical storage material. Subsequently, Chiu et al (2003) and Kim et al (2001) reported that the Ag 2 O film could be used as a mask layer to enhance the magneto-optical signal of new magnetooptical disks. Silver oxide thin films are a very interesting class of metal oxides; silver being a multivalent, forms various phases like Ag 2 O, AgO, Ag 3 O 4 and Ag 2 O 3 by interacting with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [9] reported that silver oxide films also act as a mask layer in magneto-optical disk to enhance the magneto-optical signal. However, the high threshold of thermal decomposition temperature >673 K for silver oxide films has been a bottleneck of application in optical and magneto-optical storage [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Thin films of silver oxide can be prepared by various techniques such as thermal oxidation of silver films [5], thermal evaporation [15,16], electron beam evaporation [17], pulsed laser deposition [18], chemical vapour deposition [19], electrodeposition [20], DC sputtering [8,10,[21][22][23][24][25], and RF sputtering [7,11,26,27]. Among these deposition techniques, RF magnetron sputtering is one of the promising techniques for preparation of Ag 2 O films because of the advantages of high deposition rates, uniformity on large area 2 ISRN Optics substrates, precise control on the chemical composition and physical properties.…”
Section: Introductionmentioning
confidence: 99%